Vitamin D Supplementation Guidelines for General Population and Groups at Risk of Vitamin D Deficiency in Poland—Recommendations of the Polish Society of Pediatric Endocrinology and Diabetes and the Expert Panel With Participation of National Specialist Consultants and Representatives of Scientific Societies—2018 Update - Rusińska, Agnieszka; Płudowski, Paweł; Walczak, Mieczysław; Borszewska-Kornacka, Maria K.; Bossowski, Artur; Chlebna-Sokół, Danuta; Czech-Kowalska, Justyna; Dobrzańska, Anna; Franek, Edward; Helwich, Ewa; Jackowska, Teresa; Kalina, Maria A.; et al. (Frontiers in Endocrinology, 2018)
Introduction: Vitamin D deficiency is an important public health problem worldwide. Vitamin D deficiency confers a significant risk for both skeletal and non-skeletal disorders and a number of lifelong negative health outcomes. The objectives of this evidence-based guidelines document are to provide health care professionals in Poland an updated recommendations for the prevention, diagnosis, and treatment of vitamin D deficiency. Methods: A systematic literature search examining the prevention and treatment strategies for vitamin D deficiency was conducted. Updated recommendations were developed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system describing the strength of the recommendation and the quality of supporting evidence. Twenty-seven contributors representing different areas of expertise and medical specialties, including pediatricians, geriatricians, endocrinologists, epidemiologists, nephrologists, gynecologists and obstetricians evaluated available published evidence related to vitamin D, formulated the goals of this document, and developed a common consolidated position. The consensus group, representing 6 national specialists consultants and 8 Polish and international scientific organizations/societies, participated in the process of grading evidence and drawing up the general and specific recommendations. Results: The updated recommendations define the diagnostic criteria for the evaluation of vitamin D status and describe the prevention and treatment strategies of vitamin D deficiency in the general population and in groups at increased risk of the deficiency. Age- and weight-specific recommendations for prevention, supplementation and treatment of vitamin D deficiency are presented, and detailed practice guidance is discussed regarding the management in primary and specialized health care. Conclusion: Vitamin D deficiency remains still highly prevalent in Poland, in all age groups. Currently, there is a great necessity to implement a regular supplementation with recommended doses, and to develop an effective strategy to alleviate vitamin D deficiency in the population. These updated recommendations are addressed to health professionals and the authorities pursuing comprehensive health policies, and should be also included in public health programs aimed at preventing a broad spectrum of chronic diseases.